Financing human-centred COVID-19 recovery and decisive climate action worldwide: International cooperation's twenty-first century moment of truth - Richard Samans (International Labour Organization (ILO), 2021)
This Working Paper provides a concrete illustration of how the existing international financial architecture could be activated more fully to mobilize the large sums required to respond decisively to the 'great divergence' in COVID-19 crisis recovery between advanced and developing countries as well as to the climate crisis. @International cooperation and financing for development in particular face a moment of truth. A lack of national capacity to combat the COVID-19 pandemic and climate change anywhere is a threat to the security and well-being of people everywhere. The most feasible way to mobilize the large additional sums required to advance a fully inclusive, human-centred recovery from the pandemic and a rapid acceleration of climate action on a worldwide basis - including in resource-constrained low-and lower-middle-income countries - is for the international community to apply the public capital it has already invested in the International Monetary Fund and multilateral development banksmore efficiently and expansively. This could be achieved by applying the balance sheets and tools of these institutions just as imaginatively for such common purposes as those of central banks and treasuries in advanced countries have been applied for domestic purposes during the pandemic. The paper proposes a set of initiatives to this end in order to fully fund the WHO ACT-A/COVAX Initiative, adequately resource debt relief and restructuring, social protection floors and job-rich sustainable infrastructure and industry in these countries, and finance a global effort to avoid a lock-in of greenhouse gas emissions from coal-fired power generation, which represents the single largest and most time sensitive aspect of the climate action required to achieve the goals of the Paris climate agreement. This fuller utilization of the existing international financial architecture to implement multilaterally agreed objectives would generate an average increase in annual external flows of about 4% of GDP to 82 poorer developing countries during the next seven years, exceeding the Marshall Plan's support of Europe's efforts to "build back better" from World War II, while using such additional international assistance in a similar manner to generate complementary increases in domestic resource mobilization.
Keywords: 330; decent work; future of work; social protection; development cooperation; economic recovery; international monetary system; international cooperation; multilateral system; COVID-19; climate change